2017
DOI: 10.1038/s41558-017-0032-6
|View full text |Cite
|
Sign up to set email alerts
|

Reduced feeding activity of soil detritivores under warmer and drier conditions

Abstract: Anthropogenic warming is projected to trigger positive feedbacks to climate by enhancing carbon losses from the soil1. While such losses are, in part, owing to increased decomposition of organic matter by invertebrate detritivores, it is unknown how detritivore feeding activity will change with warming2, especially under drought conditions. Here, using four year manipulation experiments in two North American boreal forests, we investigate how temperature (ambient, +1.7 °C, +3.4 °C) and rainfall (ambient, -40% … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
129
1
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

5
3

Authors

Journals

citations
Cited by 154 publications
(134 citation statements)
references
References 53 publications
3
129
1
1
Order By: Relevance
“…We found that at high water levels, changes in soil pH, and soil CN had minor effects on the overall high values of soil microbial functions, suggesting that soil water availability is the principal driver. For instance, positive effects of high temperature on soil biological activity can only be achieved when soil water is not limited (Thakur et al, 2018), and nutrient availability can be increased by higher soil moisture via increasing diffusion of soluble organic substrates (Hungate et al, 2007). This suggests that sufficient soil water availability can mitigate other unfavorable abiotic effects, thereby increasing soil ecosystem functioning.…”
Section: Discussionmentioning
confidence: 99%
“…We found that at high water levels, changes in soil pH, and soil CN had minor effects on the overall high values of soil microbial functions, suggesting that soil water availability is the principal driver. For instance, positive effects of high temperature on soil biological activity can only be achieved when soil water is not limited (Thakur et al, 2018), and nutrient availability can be increased by higher soil moisture via increasing diffusion of soluble organic substrates (Hungate et al, 2007). This suggests that sufficient soil water availability can mitigate other unfavorable abiotic effects, thereby increasing soil ecosystem functioning.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, springtails could be a reliable proxy of soil biodiversity particularly sensitive to increasingly drying conditions (Holmstrup et al, 2018;Kaersgaard, Holmstrup, Malte, & Bayley, 2004). Moreover, increasingly warmer and drier conditions may reduce feeding of soil detritivores (Thakur et al, 2018), amplifying the effects of the treatments on decomposition rates through a drop in soil fauna activity. Indeed, previous work has shown declines associated with droughts in a variety of decomposers, including microbial communities (Sowerby et al, 2005;Yuste et al, 2011), enchytraeid earthworms, and oribatid mites (Holmstrup et al, 2012;Lindberg et al, 2002), as well as in fungivorous springtails and other invertebrates known to topdown regulate microbial communities (Crowther, Boddy, & Jones, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the observed contraction of springtail richness may represent the effect of drought throughout the entire detritusbased food web. Moreover, increasingly warmer and drier conditions may reduce feeding of soil detritivores (Thakur et al, 2018), amplifying the effects of the treatments on decomposition rates through a drop in soil fauna activity. Future experiments that simultaneously manipulate species richness and environmental factors concurrently are therefore warranted to disentangle the relative importance of biotic and abiotic factors in litter decomposition (Boyero, Cardinale, Bastian, & Pearson, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Extreme drought not only forces them to migrate to deeper soil layers, but also interferes with their 366 reproduction and development success, which is possibly the reason why they are highly susceptible to 367 drought (Siepel, 1996;Frampton et al, 2000;Wever et al, 2001;Maraldo and Holmstrup, 2010). 368 Furthermore, drought conditions entail drier food sources for detritivores, which are more difficult to 369 digest (Thakur et al, 2018). 370…”
Section: Nematode Responses 268mentioning
confidence: 99%
“…In order not to damage the sticks, a steel knife was used to 162 prepare the ground prior to insertion. Five sticks were used per plot to account for some spatial 163 heterogeneity (Thakur et al, 2018). For each sampling campaign, the bait lamina sticks were removed 164 from the soil after three weeks of exposure and directly evaluated in the field.…”
mentioning
confidence: 99%